Modeling of InP Etching Under ICP Cl2/Ar/N2 Plasma Mixture: Effect of N2 on the Etch Anisotropy Evolution. Issue 3 (21st December 2012) - Chanson, Romain; Rhallabi, Ahmed; Fernandez, Marie Claude; Cardinaud, Christophe
Abstract A 2D Monte‐Carlo etching model of InP by a Cl2/Ar/N2 plasma discharge coupled to our kinetic plasma model and sheath model have been developed. It allows prediction of geometrical and chemical profile of etched trenches versus the operating conditions. The plasma kinetic model is performed to quantify reactive species densities and fluxes of Cl, N, and positive ions. The latter are introduced as input parameters in the etching model. Under Cl2/Ar plasma mixture, the mechanism of bowing development is attributed to chemical desorption of InClx sites. The addition of nitrogen into Cl2/Ar gas mixture outline the role of nitrogen in the formation of a passivated layer on the side wall. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>